2012
DOI: 10.1186/2048-7010-1-19
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of yield differences in small-scale food crop farming systems in Cameroon

Genesis T Yengoh

Abstract: Background: In sub-Saharan Africa, small-scale farmers make up the majority of food producers. While recognizing that the yields per hectare for main food crops are generally low in small-scale food production systems in this region, there are considerable differences in yield output among individual farmers. At the very local scale, why do these differences exist? By examining factors that are associated with yield differences, policy can be better informed and tailored to respond to challenges of food produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
41
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 36 publications
2
41
0
1
Order By: Relevance
“…Particularly, farmers on densely populated parts of the country produce everything from the soil and very little remains to reinvest in soil fertility replenishment for the following year (IFPRI 2010). All these farming practices brought disturbances to the ecosystems particularly on soils by disrupting the stable natural biogeochemical processes of nutrient cycle, causing rapid nutrient depletion (Yengoh 2012) and attributing to changes on the landscape characteristics (Alemu 2015; Gebreselassie et al 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Particularly, farmers on densely populated parts of the country produce everything from the soil and very little remains to reinvest in soil fertility replenishment for the following year (IFPRI 2010). All these farming practices brought disturbances to the ecosystems particularly on soils by disrupting the stable natural biogeochemical processes of nutrient cycle, causing rapid nutrient depletion (Yengoh 2012) and attributing to changes on the landscape characteristics (Alemu 2015; Gebreselassie et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The finding by Moges et al (2013) also indicated lower SOC content in cultivated lands compared to grazing or protected forest areas which was attributed by continuous cultivation, absence of fallowing and erosion. Limited maintenance of soil chemical and physical health is very likely to result poor aggregate stability, decline of soil OM, nutrient related plant stresses and stagnation of crop yields (Gajic et al 2006;Damene 2012;Yengoh 2012) and exacerbates soil degradation. Conversely, studies by Yimer and Abdulkadir (2011), Tematio et al (2011), Oriola and Bamidele (2012) documented an improvement in soil aggregates, SOC, TN, exchangeable cations and CEC due to fallowing.…”
Section: Introductionmentioning
confidence: 99%
“…The same information also stated by [8]. Also farming practices brought disturbances to the ecosystems particularly on soils by disrupting the stable natural biogeochemical processes of nutrient cycle, causing rapid nutrient depletion [11] and attributing to changes on the landscape characteristics [1] [6].…”
Section: Introductionmentioning
confidence: 77%
“…A study by Epule et al [4] argued that, between 1975 and 2005, there were 20 years during which actual cereal A study by Epule et al [4] argued that, between 1975 and 2005, there were 20 years during which actual cereal production in Cameroon were persistently below projected/expected needed cereal production levels. Yengoh et al [5] verified the role of land management practices and the sociocultural properties of small-scale farmers in establishing differences in crop yields. In addition, Epule et al [6] verified the vulnerability of experiencing food shortages along gender and poverty lines.…”
Section: Introductionmentioning
confidence: 99%